Variasi Kata Soal "Mengapa" dalam Dialek Kedah: Satu Analisis Sintaksis1 (Jurnal Bahasa, 2011)
Previous studies on Malay dialects have focused on pronunciation and lexicality. Syntactic analysis of question words, which comprise one aspect of dialect syntax, is an interesting area to research. This is due to the nature of question words which are used to construct question sentences in various languages including dialects. These question words are usually located in two positions, namely at the beginning or end of a question sentence. Research was conducted through a field study in the state of Kedah, represented by a village in each of the east, west, north and south of the state. As a result of the research conducted, it was found that the question "mengapa" (why) in the Kedah dialect (DK) not only occupied both positions but also displayed lexical variations such as pasai pa, awat, buat pa, rokpa and sebab pa. This article thus describes the phenomenon of the question word mengapa based on the lexical variations of this dialect using syntactic analysis guided by the Minimalist Program framework (Chomsky, 1995) The study describes the question word phenomenon of DK using the OP (Operator) and VAR (Variable) factors and phenomena [≠ in situ] that cause a question word to be in situ or moved. The study found that the Minimalist can "see" the adjunct. This finding contradicts the opinion of Chomsky.